2015
DOI: 10.1515/eces-2015-0021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Of The Usefulness Of Spider Webs As An Air Quality Monitoring Tool For Heavy Metals

Abstract: Abstract:The study aims at evaluating whether webs reflect the level of air pollution measured with conventional methods. Webs of species Malthonica silvestris (l. KOCH, 1872) (Araneae: Agelenidae) were sampled. Samples were analyzed for heavy metals (Pb, Zn) content. According webs analyses and classic measurements three traffic -oriented sites in Wroclaw (South-West Poland) showed significantly higher mean concentrations of heavy metals than two other sites situated in quieter, low traffic areas. A very stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Agelenidae do not have the habit of eating their own web [24], which is an important feature, allowing to obtain clean spider web and using it for transplantation in the studied area. Webs of other Agelenids can be also used in such studies [10,11].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Agelenidae do not have the habit of eating their own web [24], which is an important feature, allowing to obtain clean spider web and using it for transplantation in the studied area. Webs of other Agelenids can be also used in such studies [10,11].…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, spider webs are a quite new tool and they are not as commonly used as other bioindicators, although they are present almost everywhere [8][9][10][11][12]. Unlike lichens, they are common in the natural environment as well as in industrialized urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…Often, only well-known heavy metals like Cd, Cu, Pb and Zn, which are expected to be derived mainly from anthropogenic sources, were regarded in spider webs (e.g. Rybak et al 2012;Rybak et al 2015). Xiao-Li et al (2006) for example found mass fractions one to two orders of magnitude higher for Cd (0.85-3.37 μg/g) and Pb (35.4-290 μg/g) in webs from Wuhan (China) than we found in this work with median mass fractions of 0.260 μg/g for Cd and 11.1 μg/g for Pb.…”
Section: Moss Bags Vs Spider Webs: Chemical Compositionmentioning
confidence: 99%
“…Agelenids do not eat their large and dense webs. This features proved to be highly useful in monitoring of air pollution in a case of heavy metals and PAHs [12][13][14][15][16].…”
Section: Spiders and Webs Descriptionmentioning
confidence: 99%